Prevention and Handling of the Crisis of Financial Systems in Banking Institutions - Zulfi Diane Zaini; Lukmanul Hakim (Universitas Lampung, 2019)
Handling of troubled banks currently carried out has been carried out coordinated by related institutions including the Ministry of Finance, Bank Indonesia, the Financial Services Authority and the Deposit Insurance Corporation, as mandated by Law Number 9 of 2016 concerning Prevention and Handling of the Financial System Crisis. Where the handling of troubled banks can be more complex and integrated not only the impact of micro and macro. So that the community can maintain its trust in banking institutions and greatly help economic activities, especially banking entrepreneurs. The problems in this research are as follows: 1) How is the Application of the Precautionary Principle in Minimizing the occurrence of Problematic Banks in Indonesia? and; 2) How is Legal Certainty in the Settlement of Problem Banks in Indonesia?The research method used to answer the problems in this study is to use a normative legal research approach which is also called theoretical legal research or dogmatic legal research because it does not review the implementation of legal implementation. The results of the research and discussion show that the application of the precautionary principle carried out by these banking institutions can make a very impactful contribution, especially in order to minimize the occurrence of good problem banks that have systemic or non-systematic impacts. In addition, legal certainty in the context of handling this troubled bank has been stated in the PPKSK Law as an attempt to resolve troubled banks.